Does repeatedly viewing overweight versus underweight images change perception of and satisfaction with own body size?. Issue 4 (1st April 2020) - Bould, Helen; Noonan, Katharine; Penton-Voak, Ian; Skinner, Andy; Munafò, Marcus R.; Park, Rebecca J.; Broome, Matthew R.; Harmer, Catherine J.
Abstract : Body dissatisfaction is associated with subsequent eating disorders and weight gain. One-off exposure to bodies of different sizes changes perception of others' bodies, and perception of and satisfaction with own body size. The effect of repeated exposure to bodies of different sizes has not been assessed. We randomized women into three groups, and they spent 5 min twice a day for a week completing a one-back task using images of women modified to appear either under, over, or neither over- nor underweight. We tested the effects on their perception of their own and others' body size, and satisfaction with own size. Measures at follow-up were compared between groups, adjusted for baseline measurements. In 93 women aged 18–30 years, images of other women were perceived as larger following exposure to underweight women (and vice versa) ( p < 0.001). There was no evidence for a difference in our primary outcome measure (visual analogue scale own size) or in satisfaction with own size. Avatar-constructed ideal ( p = 0.03) and avatar-constructed perceived own body size ( p = 0.007) both decreased following exposure to underweight women, possibly due to adaptation affecting how the avatar was perceived. Repeated exposure to different sized bodies changes perception of the size of others' bodies, but we did not find evidence that it changes perceived own size.